2019
DOI: 10.1002/chem.201902121
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Mechanisms of Aquaglyceroporin‐3 Water and Glycerol Permeation by Metadynamics

Abstract: Water and glycerolp ermeation through human AQP3 are described by exploiting advanced metadynamics approaches, which enabledb oth to explore the free energies involved in pore permeation and to achieve adescription of the mechanisms with an atomistic level of detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
4
17
0
Order By: Relevance
“…20 Recently, using metadynamics simulations, we investigated the mechanisms of glycerol permeation by the human AQP3 isoform. 21 The obtained results showed that single-file water permeation through AQP3 is always bidirectional at equilibrium conditions, and that individual water molecules are able to 'hop' over each other ('leap-frog' mechanism), whilst traveling in opposite directions in certain key areas of the pore. Such mechanism for water transport may be essential to understand aquaporins ability to switch from uptake to efflux quickly under changing physiological conditions.…”
Section: Resultsmentioning
confidence: 93%
“…20 Recently, using metadynamics simulations, we investigated the mechanisms of glycerol permeation by the human AQP3 isoform. 21 The obtained results showed that single-file water permeation through AQP3 is always bidirectional at equilibrium conditions, and that individual water molecules are able to 'hop' over each other ('leap-frog' mechanism), whilst traveling in opposite directions in certain key areas of the pore. Such mechanism for water transport may be essential to understand aquaporins ability to switch from uptake to efflux quickly under changing physiological conditions.…”
Section: Resultsmentioning
confidence: 93%
“…This aquaglyceroporin is known to be expressed in different tissues, including skin [76], respiratory tract [77], kidneys [74] and gut [78]. AQP3 has also been found to be present in distinct cancer types [79,80,81]. In melanoma, it is well-known that AQP3 is overexpressed [50,51] and researchers have shown that AQP3 knockout mice are resistant to skin tumor formation [79].…”
Section: Advancing Melanoma Systemic Treatment—potential Targets Amentioning
confidence: 99%
“…This analysis suggests that residues at the entrance of the channel may contribute to the different hydrophobicity/hydrophilicity and surface charge distribution—as observed for VvTnNIP1;1 and VvTnNIP6;1—and, together with residues of the ar/R filter, may play a relevant role in determining NIP substrate selectivity. It is worth mentioning that other computational studies on the interaction of human aquaglyceorporins with glycerol and selective small-molecule inhibitors highlighted the pivotal role of the chemical composition of the extracellular AQP’s pocket in modulating the affinity of the protein channel towards its substrate/inhibitor via the establishment of numerous non-covalent interactions [ 29 , 30 ]. The latter cannot be excluded to play a role in the selectivity of NIPs for certain substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Recent metadynamics studies showed that glycerol permeation in human aquaporins experiences the highest energy barrier in the NPA filter. Overall, the substrate transport was found to critically depend on bond switches within a dynamic hydrogen-bond scaffold created by the interplay of glycerol, water molecules and pore amino acid residues, disclosing a novel scenario, in which substrate molecules exploit an existing water conduction mechanism [ 30 ]. Therefore, it would be worth to carefully evaluate also the effects of the NPA selectivity filter on grapevine NIPs’ substrate selectivity.…”
Section: Discussionmentioning
confidence: 99%